Liver Condition Affects Bovine Oocyte Qualities by Changing the Characteristics of Follicular Fluid and Plasma. Issue 4 (3rd January 2013) - Tanaka, H; Shibano, K; Monji, Y; Kuwayama, T; Iwata, H
Contents: The liver is an important organ that contributes to milk production in dairy cows. The aim of this study was to examine whether liver conditions affect the characteristics of blood plasma and follicular fluid (FF) and whether supplementing in vitro maturation medium with FF from either cows with damaged livers (DL) or those with healthy livers (HL) affects oocyte developmental competence. Biochemical characteristics of FF were significantly correlated with those in plasma. As such, the characteristics of both plasma and FF were similarly affected by liver conditions in that the concentrations of total protein and inorganic phosphorus were higher for the DL cow group than for the HL cow group, whereas the concentrations of albumin, lactate dehydrogenase and calcium were lower for DL cows than for HL cows. In addition, supplementing the medium with DL‐FF retarded the progression of the nuclear maturation of oocytes collected from the HL cows. On culturing oocytes in maturation medium containing HL‐FF, DL‐FF or foetal calf serum, the highest developmental rate to the blastocyst stage was observed in the HL‐FF group, while the lowest developmental ratio was observed in the DL‐FF group. The growth factor array of the FFs revealed that 10 growth factors were significantly downregulated in the DL‐FF compared with those in HL‐FF. In conclusion, the characteristics of plasma and FF are affected by liver conditions in a similar way. Concentrations of several growth factors were low in DL‐FF, as was the ability of DL‐FF to support oocyte maturation compared with that of HL‐FF.